2019
DOI: 10.1016/j.ijcard.2018.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Pre-participation cardiovascular evaluation in Pacific Island athletes

Abstract: Background: Pre-participation cardiovascular evaluation (PPE) aims to detect cardiac disease with sudden cardiac death (SCD) risk. No study has focused on Pacific Island athletes. Methods: A total of 2 281 Pacific Island athletes were studied with (i) a questionnaire on family, personal history and symptoms, (ii) a physical examination and (iii) a 12-lead ECG. Results: 85% presented a normal history and examination. A positive family history was 1.4-1.9 fold higher in Melanesians, Polynesians and Métis than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Pacific Islander athletes were assessed in four papers [ 38 , 44 , 61 , 62 ], summarized in Table 8 . In one study, Melanesian athletes were reported to be twice as likely as other Pacific Islanders and Caucasian athletes to have TWI, comparable to Afro-Caribbean athletes [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pacific Islander athletes were assessed in four papers [ 38 , 44 , 61 , 62 ], summarized in Table 8 . In one study, Melanesian athletes were reported to be twice as likely as other Pacific Islanders and Caucasian athletes to have TWI, comparable to Afro-Caribbean athletes [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pacific Islander athletes were assessed in four papers [ 38 , 44 , 61 , 62 ], summarized in Table 8 . In one study, Melanesian athletes were reported to be twice as likely as other Pacific Islanders and Caucasian athletes to have TWI, comparable to Afro-Caribbean athletes [ 62 ]. In this study, 11 Pacific Islander groups were assessed, finding that 14% had LVH and 7.4% had right-ventricular hypertrophy (RVH), a similar prevalence to Caucasian athletes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term cardiovascular mortality data were reported by three articles. 27,31,45 In the SWiM, we identified 11 167/82 417 (13.5%) athletes with screening abnormalities needing additional testing, such as ECG and TTE-if not performed-CMR or genotyping. Across the different strategies 22.1% were found through H-PE (2188/9898), 19.7% through H-PE-ECG (6374/32 369), and 6.5% through H-PE-ECG-TTE (2605/40 148), respectively (Figure 2).…”
Section: Screening Efficacy Swim Analysismentioning
confidence: 99%
“…Nearly all data on cardiovascular screening and incidence of SCD in young athletes have come from Europe or the United States, so the study by Chatard et al [8] on preparticipation cardiovascular evaluation among Pacific Island athletes published in this issue of the Journal is a welcomed addition to the rapidly growing literature on this somewhat emotional and controversial subject. The authors should be commended for conducting a study in this sparsely populated area spanning thousands of kilometers, although this lead to some difficulties in investigating the abnormal findings further, potentially affecting the results.…”
mentioning
confidence: 99%